NON-STANDARD FORMS AND METHODS OF TEACHING RUSSIAN LANGUAGE CLASSES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The role of the Russian language among the languages of the "world" is a means of international communication as very large. In the 20th - 21st centuries, the socio-political, economic, scientific. Due to the entire direction of technical and cultural development, the Russian language is rightfully the world is considered This is primarily explained by the "international" of modern science. Nature and the unprecedented pace of its development. Every now and then it is important that the student knows the Russian language well. In this regard, teaching the Russian language it is important to use new methods.